√3x+6 (+6 is in radical)= x-4

- anonymous

√3x+6 (+6 is in radical)= x-4

- Stacey Warren - Expert brainly.com

Hey! We 've verified this expert answer for you, click below to unlock the details :)

- schrodinger

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

- anonymous

square both sides to get rid of square root

- anonymous

square (x-4)---FOIL

- anonymous

\[3x + 6 = x^{2} -8x + 16\]

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

- anonymous

subtract 3x and 6 to move to right side leaving 0 on the left

- anonymous

\[x^{2} -11x - 10 =0\]

- anonymous

you can factor using chart or my grouping

- anonymous

sorry that should be +10

- anonymous

\[x^{2} - 11x + 10 =0\]

- anonymous

what factors of 10 as a product gives you -11 as a sum?
-1 * -10=10 and -1 + (-10)=-11

- anonymous

so the factors are -1 and -10
(x-1)(x-10)=0
x-1 = 0 and x-10=0
x=1 x=10
{1, 10}

- anonymous

or factoring by grouping-break down middle term using know factors of -1 and-10

- anonymous

\[x^{2}-x-10x+10\]

- anonymous

factor out GCF
x(x-1)-10(x-1)=0
(x-10)(x-1)=0
x=10 and x=1

- anonymous

thx

- anonymous

welcome...do you understand? what grade are you in...medal please ; )

- anonymous

im in 8th doing algebra, so what ur final answer?

- anonymous

and what are you talking about with a medal?

- anonymous

love 8th grade Algebra! Solutions are 10 and 1
{1, 10}

- anonymous

click on good answer by my name on the right

- anonymous

yeah i got that, but when you plug it back in, it doesnt work. does it have to work?

- anonymous

what answer do i click on for good answer?

- anonymous

it does work

- anonymous

\[x=1 \sqrt{9}=1-4\]

- anonymous

okay good, thanks for your help

- anonymous

square root of 9 is 3 or -3

- anonymous

wait could u also help me with another question instead of me reposting one??

- anonymous

sure

- anonymous

x=10 so square root of 36 equals -6 or 6

- anonymous

a right triangle has one leg that is 4 inches shorter than the other leg. the hypotenuse is √106 inches. find the lengths of the legs.

- anonymous

ok i'm writing it out to solve...hold on

- anonymous

k

- anonymous

ill be right back

- anonymous

do you want to factor my grouping

- anonymous

\[2x^{2}-8x-90=0\]

- anonymous

let a = x, b=(x-4) and c=square root of 106(hypotenuse)

- anonymous

\[x^{2} + x^{2} -8x +16 = 106\]

- anonymous

after plugging into Pythagorean Theorem (right triangle)

- anonymous

subtract 106 from both sides to get the first equation I posted above

- anonymous

back

- anonymous

working backwards so hope you can follow

- anonymous

kind of

- anonymous

where did you get lost?

- anonymous

http://www.twiddla.com/536745 go there for explanation

- anonymous

thx

Looking for something else?

Not the answer you are looking for? Search for more explanations.